Diffusing-wave spectroscopy in randomly inhomogeneous media with spatially localized scatterer flows. - Skipetrov, S. E.; Meglinski, I. V. (Springer Science Business Media, 1998)
Multiple scattering of laser radiation in a randomly inhomogeneous turbid medium with a spatially localized flow of particles is studied. The time autocorrelation function of backscattered light is calculated for the case of a laminar flow of scatterers in a cylindrical capillary embedded in the medium. A new method is proposed and tested experimentally for determining the position of the dynamic region and the dominant form and characteristic velocity of the particle motion there.